The impact of leadership styles on employees commitment towards innovative behavior in private sector, Kuching, Sarawak - Adrian Goh Sze, Liang (Universiti Malaysia Sarawak, 2019)
This research aims to explore the impact of three leadership styles from the New Leadership Paradigm, transformational, transactional and laissez-faire leadership style on employees' commitment and towards their innovative behaviour. A total of four hypotheses was formulated to analyse the effect among employees from private sectors organizations from different industry in Kuching, Sarawak. The data was acquired from the employees by self-administrated questionnaire. The results analysed shows that transformational leadership style (TFL) and transactional leadership style (TSL) has a positive and significant relationship towards employees' commitment (EC), however, laissez-faire leadership style (LFL) shows a negative relationship with employees' commitment (EC). The analysation between employees' commitment (EC) and innovative behaviour (IB) shows a positive and significant relationship between the two variables. Hence, the findings provide support for how does different types of leadership styles affects employees' commitment and towards their innovative behaviour in the context of private sector organization in Kuching, Sarawak.